Fighting Disinformation: The role of civil society and collective intelligence in the Brasilian presidential election - Thamy Pogrebinschi; Maria Dominguez; Mariana Borges Martins da Silva (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2022)
Disinformation increasingly threatens democracy. How can this be prevented? Regulating platforms is often not enough to contain the dangers of disinformation for political processes. Thamy Pogrebinschi, Maria Dominguez and Mariana Borges Martins da Silva have examined the role civil society and collective intelligence can play in the fight against disinformation using the example of Brazil.
Keywords: 300